2004
DOI: 10.1152/jn.00466.2004
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ifenprodil Against Spreading Depression in the Mouse Entorhinal Cortex

Abstract: Faria, Leonardo Coutinho and Istvan Mody. Protective effect of ifenprodil against spreading depression in the mouse entorhinal cortex. J Neurophysiol 92: 2610 -2614, 2004. First published June 16, 2004 10.1152/jn.00466.2004. In the brain, spreading depression (SD) is characterized by a large extracellular DC shift, a massive failure of ion homeostasis and a transient cessation of neuronal function. Clinically, SD is believed to be involved in various neurological disorders including migraine and cerebrovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
(20 reference statements)
2
18
2
Order By: Relevance
“…That Menniti et al (2000) blocked SD completely with CP-101,606, whereas the blockade we observed was incomplete, may be due to the precise methods of SD initiation. Our results also complement literature findings with the NR2B-selective antagonist ifenprodil in spontaneous SD generated in mouse entorhinal cortex slice preparations (Faria and Mody, 2004). Given the significant brain concentrations achieved, as discussed above, why do memantine, CP-101,606, and Ro 25-6981 not block SD completely?…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…That Menniti et al (2000) blocked SD completely with CP-101,606, whereas the blockade we observed was incomplete, may be due to the precise methods of SD initiation. Our results also complement literature findings with the NR2B-selective antagonist ifenprodil in spontaneous SD generated in mouse entorhinal cortex slice preparations (Faria and Mody, 2004). Given the significant brain concentrations achieved, as discussed above, why do memantine, CP-101,606, and Ro 25-6981 not block SD completely?…”
Section: Discussionsupporting
confidence: 88%
“…Since Marrannes et al (1988) confirmed that NMDA-R is an important component in the generation and propagation of SD and associated inward currents, a variety of NMDA-R antagonists have been shown to block cortical SD (Marrannes et al, 1988;Lauritzen and Hansen, 1992;Anderson and Andrew, 2002). The role of NMDA [but not kainate or AMPA (␣-amino-3-hydroxy-5-methyl-4-isoxazole propionate) receptors] in SD is suggested by the abilities of MK-801 (dizocilpine) and SKF-10047 (noncompetitive NMDA-R ion channel blockers) (Willette et al, 1994) and L-701,324 and ZD9379 (antagonists of the glycine site of the NMDA-R complex) (Obrenovitch and Zilkha, 1996;Tatlisumak et al, 1998), and CP-101,606 (traxoprodil) and ifenprodil (NR2B subunit-selective antagonists) (Menniti et al, 2000;Faria and Mody, 2004) to inhibit SD initiation and propagation.…”
mentioning
confidence: 99%
“…However, in brain slices of mouse entorhinal cortex, the NR2B specific antagonist ifenprodil prevented CSDs from occurring (Faria and Mody, 2004). In our experiments, NR2A antagonist TCN-201 was not effective, as it did not influence the CSD BOLD response shape.…”
Section: Discussioncontrasting
confidence: 69%
“…In this study, we found that induction of SD in rat hippocampal slices in vitro by focal elevation of [K + ] o results in a similar pattern of spine shrinkage and retraction, followed by recovery of spines once the wave of depolarization has passed and membrane potential recovers, consist with findings in neocortex of Takano et al (2007). NMDA glutamate receptor (NMDAR) activation can promote, or even be essential for, the phenomenon of SD in many experimental situations (Anderson and Andrew, 2002;Faria and Mody, 2004;Gill et al, 1992;Hartings et al, 2003;Peeters et al, 2007). NMDAR blockers such as ketamine can, at least temporarily, block SD (Amemori and Bures, 1990;Hernandez-Caceres et al, 1987;IIjima et al, 1992;Lauritzen and Hansen, 1992).…”
supporting
confidence: 56%
“…Previous studies have suggested that activation of NMDARs can be an important contributor to the generation and propagation of SD (Anderson and Andrew, 2002;Faria and Mody, 2004;Gill et al, 1992;Hartings et al, 2003;Peeters et al, 2007), and that NR2B subunit-containing NMDARs may be particularly involved under some conditions (Faria and Mody, 2004). At the same time, stimuli such as stroke (Murphy et al, 2008), oxygen/glucose deprivation (Jourdain et al, 2002) and NMDAR-dependent LTD of synaptic strength (Zhou et al, 2004), can trigger persistent shrinkage of dendritic spines in hippocampus that can be either completely, or partially, reversible.…”
Section: Discussionmentioning
confidence: 99%